Regulation of the transmission characteristics of terahertz metamaterials based on CS2 - Shi Yilin (Dianzi Jishu Yingyong, 2019)
At present, optically controlled terahertz band metamaterials are mainly realized by changing the carrier concentration of semiconductor materials with laser. The composite lifetime of semiconductor materials is generally in nanosecond order, which limits the controlling time. Compared with semiconductor materials, CS2 has a fast light response time of about 1.68 ps and large optical nonlinearity. Based on the structure of sub-wavelength periodic metal block arrays, a strategy to adjust terahertz transmission of metamaterials using CS2 is proposed. Specifically, the control of terahertz wave transmission in this structure is studied by finite difference time domain(FDTD).